The Influence of Financial Behavior and Financial Experience on Financial Literacy among Generation Z: JEL Classification: D14, G53, I21, A20 - Khasanah, Uswatun; Puspitasari, Intan; Utomo, Agus Saur (Journal La Bisecoman, 2025)
Financial literacy plays a crucial role in supporting sustainable development and is a fundamental need for individuals in managing their finances. Although Generation Z (Gen Z) is considered tech-savvy, this skill does not always correlate with a high level of financial literacy. The main challenge faced by Gen Z is the increasing temptation of consumerism, driven by various digital facilities such as e-commerce apps and electronic payment services, which make spending easier without proper planning. Despite their relatively high financial literacy, consumer behavior influenced by digital technology remains an obstacle. This study aims to analyze the impact of financial behavior and financial experience on the level of financial literacy among Gen Z, who play a significant role in the digital economy. This research is a quantitative study with a survey approach. The purposive sampling technique was used to select the research sample, with a sample size of 160 respondents calculated using the Hair formula. Data collection was conducted by distributing questionnaires to Gen Z respondents (born between 1995-2012) who are pursuing higher education (diploma or bachelor’s degree) at colleges or universities and reside in Purworejo Regency. The data analysis technique used is quantitative analysis with multiple linear regression analysis method using smartPLS 3.3.9 software. The research findings show that financial behavior and financial experience have a positive and significant partial impact on financial literacy among Generation Z in Purworejo. Therefore, it is important to enhance Generation Z's understanding and involvement in daily financial activities to strengthen their financial literacy.